Answer:
-7 3=-4
-5 1=-4
-3 -1=-4
-7 and 3 make -4. -5 and 1 make -4. -3 and -1 make -4.
Answer:
Ok:
Step-by-step explanation:
So f°g . means f(g(x)). (The ° should be more center and bigger but I don't know to do that on a keyboard). f(g(x)) means that you replace the x in f(x) with the g(x) function. i.e:
if f(x) = 2x+2
and g(x) =
f(g(x)) = .
Similarly, in this case, we get f(x) = 2x-3 and g(x) = 3x-2.
Then, f(g(x)) or f°g(x) is 2(3x-2) - 3.
And we plug in -2 to solve:
2(3(-2)-2)-3.
and get -19.
Check if I am wrong because everyone makes mistakes but that is the way to solve this.
U plug in the y
2 (3x) -5x=4
simplify
6x -5x =4
solve
x=4
so now you know x=4 so plug that in for x
y= 3(4)
y=12
check your answer
2(12)-5(4)=4
solve
24-20=4
4=4
so you now you got the answer right !
hope that helps!
Your answer is B. 0.075 m
Answer:
was there more
Step-by-step explanation:
(i will edit answer)